Unilateral Cancellation of Joint Property Sales After Divorce According to Civil Law - Mhd. Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the underlying considerations of judges in canceling sales agreements of joint property that has not yet been divided after a divorce, as well as to analyze the legal reasoning behind the judges’ decisions. The research method used is Normative Legal Research, employing a Library Research approach and a Statutory Approach, along with Interview Methods (file research). The basis for the judges’ decisions in this case is that both the seller and the buyer acted without good faith. As a result, there is still an aggrieved party, namely the plaintiff, who is the former wife of the seller, because the item sold was still classified as joint property. Every individual, community, or even state engaging in a sale—whether large or small scale—must ensure that the origin and purpose of the item being sold are clear so that no other parties are harmed. In this case, the item sold was still joint property, but it was sold without the consent of one of the parties, which led the judge to annul the transaction. Selling joint property without the approval of both spouses after a divorce is considered legally flawed and constitutes the criminal act of embezzlement. Such an act may be subject to a maximum imprisonment of four years and a Class IV fine of IDR 200,000,000 (two hundred million rupiah). Thus, it can be concluded that before conducting any sale, it is essential to verify whether the item is joint property to avoid potential legal disputes in the future.